A Study of the Computer Programming Language Implementation in Computer Engineering Students using the Flowgorithm Platform versus Common Programming - bounpaserth, somchit; kounlaxay, kalaphath; manivanh, vialakone; simmavong, southeva (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The evaluation of students’ programming abilities and performance using the Flowgorithm Platform revealed that the participants were first assessed on their basic programming knowledge through pre-tests and exercises. Afterward, instruction on the use of Flowgorithm was introduced, including examples of problem analysis and the design of flowcharts in a step-by-step process. Following the training sessions, students completed actual post-tests to evaluate their performance before and after the training. The results showed that post-training test scores improved significantly compared to pre-training scores. Individual performance analysis was also conducted through exercises and tests involving problem analysis and flowchart design using the Flowgorithm software. The comparison of students’ programming abilities and performance using the Flowgorithm Platform showed the following results the Sequence Flowchart problem-solving test, the average pre-training score was X̄ = 70.13, while the post-training average score increased to X̄ = 87.23. the Selection Flowchart problem-solving test, the average pre-training score was X̄ = 63.47, while the post-training average score increased to X̄ = 81.17. Loop Flowchart problem-solving test, the average pre-training score was X̄ = 64.77, while the pot-training average score increased to X̄ = 80.00.